Subdiaphragmatic bronchogenic cysts: Case series and literature review - Xiao, Jianchun; Zhang, Xueyang; Zhou, Hongru; Hong, Tao; Li, Binglu; He, Xiaodong; Liu, Wei (Frontiers in Medicine, 2022)
Bronchogenic cysts are congenital malformations caused by aberrant foregut budding. They major occur in the thorax, with subdiaphragmatic cases being uncommon. Here, we present a series of 19 patients diagnosed with subdiaphragmatic bronchogenic cysts histopathologically at a single institution in China from 2012 to 2021. A literature review was also conducted by searching the PubMed database using keywords related to “bronchogenic cysts” and “subdiaphragmatic”, yielding 107 cases. Taken together, the 126 cases had a median age of 41.0 years (interquartile range, 30.0-51.0 years) and 62 of them were male (49.2%). The cysts were most commonly detected in the left adrenal region (36.2%), followed by the pancreatic region (11.5%) and gastric cardia/lesser curvature of the stomach (9.2%). All patients except two underwent surgery for a definite diagnosis, symptoms alleviation, and (or) malignancy prevention. Most patients recovered fast and were discharged from the hospital within one week after surgery, and the surgical complications were infrequent. The prognosis was generally favorable, as no recurrence was reported during the follow-up as long as 77 months.